Silica-supported sulfonic acids as recyclable catalyst for esterification of levulinic acid with stoichiometric amounts of alcohols - Maggi, Raimondo; Shiju, N. Raveendran; Santacroce, Veronica; Maestri, Giovanni; Bigi, Franca; Rothenberg, Gadi (Beilstein Journal of Organic Chemistry, 2016)
Converting biomass into value-added chemicals holds the key to sustainable long-term carbon resource management. In this context, levulinic acid, which is easily obtained from cellulose, is valuable since it can be transformed into a variety of industrially relevant fine chemicals. Here we present a simple protocol for the selective esterification of levulinic acid using solid acid catalysts. Silica supported sulfonic acid catalysts operate under mild conditions and give good conversion and selectivity with stoichiometric amounts of alcohols. The sulfonic acid groups are tethered to the support using organic tethers. These tethers may help in preventing the deactivation of the active sites in the presence of water.
Keywords: esterification; heterogeneous catalysis; renewable feedstocks; supported organic catalysts; sustainable chemistry